Mulberroside A mitigates intervertebral disc degeneration by inhibiting MAPK and modulating Ppar-γ/NF-κB pathways - Tao Xu; Hongqi Zhao; Xuan Fang; Shanxi Wang; Jian Li; Hua Wu; Weihua Hu; Rui Lu (BMC, 2024)
Abstract Background Intervertebral disc degeneration (IVDD) is a common spine disease with inflammation as its main pathogenesis. Mulberroside A (MA), isolated from herbal medicine, possesses anti-inflammatory characteristics in many diseases. Whereas, there is little exploration of the therapeutic potential of MA on IVDD. This study aimed at the therapeutic potential of MA on IVDD in vivo and in vitro and the mechanism involved. Methods In vitro, western blotting, RT-qPCR, and immunofluorescence analysis were implemented to explore the bioactivity of MA on interleukin-1 beta (IL-1β)-induced inflammation nucleus pulposus cells (NPCs) isolated from Sprague-Dawley male rats. In vivo, X-ray and MRI were applied to measure the morphological changes, and histological staining and immunohistochemistry were employed to investigate the histological changes of intervertebral disc sections on puncture-induced IVDD rat models. Results In vitro, MA up-regulated the expression level of anabolic-related proteins (Aggrecan and Collagen II) and decreased catabolic-related proteins (Mmp2, Mmp3, Mmp9, and Mmp13) in IL-1β-induced NPCs. Furthermore, MA inhibits the production of pro-inflammatory factors (Inos, Cox-2, and Il-6) stimulated by IL-1β. Mechanistically, MA inhibited the signal transduction of mitogen-activated protein kinase (MAPK) and nuclear factor kappa-B (NF-κB) pathways in IL-1β-induced NPCs. Moreover, MA might bind to Ppar-γ and then suppress the NF-kB pathway. In vivo experiment illustrated that MA mitigates the IVDD progression in puncture-induced IVDD model. X-ray and MRI images showed MA restore the disc height and T2-weighted signal intensity after puncturing. H&E and Safranin O/Fast Green also showed MA also alleviated morphological changes caused by acupuncture. In addition, MA reversed the expression level of Mmp13, Aggrecan, Collagen II, and Ppar-γ induced in IVDD models. Conclusions MA inhibited degenerative phenotypes in NPCs and alleviated IVDD progression via inhibiting the MAPK and NF-κB pathways; besides, MA suppressed the NF-κB pathway was attributed to activating Ppar-γ, those supported that MA or Ppar-γ might be a potential drug or target for IVDD.